Curcumin: a natural organic component that plays a multi-faceted role in ovarian cancer - Xiaoping Liu; Mingming Qi; Xidie Li; Jingjin Wang; Mingyuan Wang (BMC, 2023)
Abstract Curcumin, a natural organic component obtained from Curcuma longa's rhizomes, shows abundant anti-tumor, antioxidant and anti-inflammatory pharmacological activities, among others. Notably the anti-tumor activity has aroused widespread attention from scholars worldwide. Numerous studies have reported that curcumin can delay ovarian cancer (OC), increase its sensitivity to chemotherapy, and reduce chemotherapy drugs' side effects. It has been shown considerable anticancer potential by promoting cell apoptosis, suppressing cell cycle progression, inducing autophagy, inhibiting tumor metastasis, and regulating enzyme activity. With an in-depth study of curcumin's anti-OC mechanism, its clinical application will have broader prospects. This review summarizes the latest studies on curcumin's anti-OC activities, and discusses the specific mechanism, hoping to provide references for further research and applications.